Preduodenal portal vein associated with duodenal obstruction as a part of polysplenia syndrome in preadolescent girl - Tarek Talaat Harb Elkadi; Zahra Al Matar; Ghaida Al Abidi (Elsevier, 2021)
Preduodenal portal vein is a rare congenital vascular disorder that causes duodenal obstruction. In this case report, we discuss late presentation of duodenal obstruction resulting from this anomaly in a preadolescent female with cerebral palsy.The incomplete and late presentation of preduodenal portal vein creates a surgical dilemma. Awareness of this anomaly is critical and should be kept in consideration for all cases of duodenal obstruction.